Development of Rapid Alignment Polisher’s Hand (RAPH) for Cross section Polishing in Physical Failure Analysis - Handie, Ahmataku (Universiti Malaysia Sarawak, 2024)
X-FAB uses patented process technology to produce analog/mixed-signal ICs. As a pure-play foundry, X-FAB does not produce its own integrated circuits (ICs), instead manufacturing them using designs produced by its clients or other parties in collaboration, mostly using X-FAB's portfolio of modular, highly specialized proprietary process technologies and intellectual property (IP). Chemical Mechanical Polishing (CMP) cross-sectioning technique has been recognized for many years as failure analysis fundamental tool for examining depth-related profile of a sample. Therefore, it is a precious tool in semiconductor industry as its exclusive characteristic of providing entry into a third dimension in a two-dimension world. Process levels can be micro sectioned and capability to inspect layer-by-layer made this method crucial in gathering information on fabrication parameters and on defects. Another advantage of CMP cross-sectioning is its wide area of observation as compared to other cross-sectioning methods such as Focus Ion Beam (FIB). CMP cross-sectioning requires high skilled failure analyst and require couple of hours to complete a section of reasonable complexity of target. Typically, CMP cross-sectioning is performed in three basic steps: physical mounting, coarse grind and final polish. These three steps are time consuming particularly during coarse grind, the analyst need to realign the target before it reaches to final polish. Any technology that can reduce the polishing turnaround time is most welcomed on this day. Allied High-Tech Products. Inc. is a well-known maker of precision grinders and polishers. This research will provide a new idea of design and fabrication of the anticipated polisher fixture called Rapid Alignment Polisher Stage (RAPH), which will assist a fast, controllable, and accurate target alignment which current method is lacked off. This product is believed able to decrease the polishing turnaround time significantly.